Mapping the landscape of land inequality: A multi-level, data-driven exploration of land inequality in South Korea's urban and regional spheres. - Yookyung Lee; Seungwoo Han (PLoS ONE)
Land inequality has emerged as a defining challenge in contemporary societies, shaping patterns of wealth concentration and socioeconomic stratification. This study critically examines the persistence and intensification of land disparities in South Korea between 2018 and 2022, applying a data-driven methodological framework to uncover structural inequalities embedded within the spatial distribution of land wealth. The analysis reveals a stark divergence in property values and ownership patterns, reinforcing existing socioeconomic divisions and highlighting the spatial entrenchment of privilege. The implications of these disparities extend beyond economic inequities, raising concerns about long-term social stability and policy effectiveness in mitigating wealth concentration. This study underscores the necessity of policy interventions to address the compounding effects of land inequality. By advancing an empirical approach to the study of land concentration, this research contributes to broader discussions on spatial inequality, economic polarization, and sustainable urban development.